Case report: Compound heterozygosity in PKLR gene with a large exon deletion and a novel rare p.Gly536Asp variant as a cause of severe pyruvate kinase deficiency - Kim, Minsun; Lee, Seung Yeob; Kim, Namsu; Lee, Jaehyeon; Kim, Dal Sik; Park, Joonhong; Cho, Yong Gon (Frontiers in Pediatrics, 2022)
Red cell pyruvate kinase (PK) deficiency is the most common cause of hereditary non-spherocytic hemolytic anemia and the most frequent enzyme abnormality of the glycolytic pathway. To the best of our knowledge, this is the first Korean PK deficiency study that analyzes copy number variation (CNV) using next-generation sequencing (NGS). A 7-year-old girl with jaundice was admitted for evaluation of a persistent hemolytic anemia. The proband appeared chronically ill, showing a yellowish skin color, icteric sclera, hepato-, and splenomegaly on physical examination. Sequence variants and CNV generated from NGS data were estimated to determine if there was a potential genetic cause. As a result, compound heterozygosity in PKLR gene for a large exon deletion between exon 3 and exon 9 accompanied with a novel rare p.Gly536Asp variant located on exon 10 was identified as a cause of severe PK deficiency in the proband. The PK activity of the proband had been measured at the time of day 1, 21, and 28 after receiving transfusion to indirectly assume the effect of the transfused blood, and the results were 100.9%, 73.0%, and 48.5%, compared with average of normal controls, respectively. Our report emphasizes the need to perform complete CNV analysis of NGS data and gene dosage assays such as MLPA to evaluate large deletions or duplications/insertions of the PKLR gene in patients with suspected PK deficiency.